Chronic diarrhoea after radiotherapy for gynaecological cancer: occurrence and aetiology. Issue 10 (October 1991) - Danielsson, A; Nyhlin, H; Persson, H; Stendahl, U; Stenling, R; Suhr, O
Abstract : The occurrence of chronic diarrhoea was evaluated in 173 consecutive patients previously treated with radiation for gynaecological cancer. A survey of gastrointestinal symptoms showed a high frequency of diarrhoea; 13% of the patients had 21 or more bowel movements a week and 3% had 28 or more. Significantly more patients who had a cholecystectomy were in the group with diarrhoea (chi 2 = 6.26; p less than 0.02). Twenty patients with chronic or intermittent diarrhoea were subject to extended gastrointestinal investigation. Bile acid malabsorption was evaluated by the 75Selenahomocholic acid-taurine test (SeHCAT). Bile acid malabsorption was found in 13 (65%) of the 20 patients further investigated, of whom seven had extremely low whole body retention values, which is consistent with severe malabsorption. The results suggest that bile acid malabsorption is a common cause of diarrhoea after radiation treatment for gynaecological cancer. Bacterial contamination was diagnosed in nine patients (45%) by the [14C]-D-xylose breath test or by the cholyl-[14C]-glycine breath test in combination with a normal test for bile acid malabsorption. All patients with vitamin B-12 deficiency, who were tested for bile acid malabsorption, had low retention times for the SeHCAT (p = 0.05). A significant decline in the frequency of diarrhoea was found after treatment with antibiotics or bile acid sequestrants, or both, in combination with a reduced fat diet.